Contribution of AE analysis in order to evaluate time to failure of ceramic matrix composites. (1st April 2019) - Godin, Nathalie; Reynaud, Pascal; Fantozzi, Gilbert
Highlights: Novel analysis of acoustic emission in order to evaluate the time to failure. Linear correlation between characteristics time based on AE (around 50% of the total test duration) and time to failure. Comparison between several empiric approach for lifetime predictions on CMC during static fatigue. Abstract: The paper presents an empirical approach to obtain the Remaining Useful Lifetime (RUL) or Time To Failure (TTF) using mechanical parameters or Acoustic Emission (AE) of Ceramic Matrix Composite (CMC) submitted to static fatigue tests at the laboratory scale. The approach is based on the investigation of the AE dynamic and identification of characteristic times with several indicators such as the sentry function, coefficient RAE, coefficient of attenuation B. A linear correlation is established between these characteristics times and the time to failure allowing the possibility of evaluating the Time To Failure in real time. The results are compared to those obtained with mechanical parameters such as the strain and the damage parameter.